Global Epidemiology of Meningococcal Disease-Causing Serogroups Before and After the COVID-19 Pandemic: A Narrative Review - Steven Shen; Jamie Findlow; Paula Peyrani (Infectious Diseases and Therapy)
Abstract Invasive meningococcal disease (IMD) is associated with high morbidity and mortality and predominantly caused by five Neisseria meningitidis serogroups (A/B/C/W/Y). Polysaccharide conjugate vaccines induce T-cell-dependent immune responses, are immunogenic in infants and adults, and reduce carriage, and vaccination of age groups associated with high-carriage can provide indirect protection in the unvaccinated (herd immunity). Successful vaccination programs must be tailored to local epidemiology, which varies geographically, temporally, and by age and serogroup. Serogroup A IMD once predominated globally, but has largely disappeared following mass vaccination programs. Serogroup B was a predominant cause of IMD in many global regions from 2010 to 2018, typically affecting younger age groups. Spread of serogroup C clonal complex-11 IMD in the 1990s prompted implementation of MenC vaccine programs in many countries, resulting in declines in prevalence. Serogroup C still caused > 20% of global IMD through the mid-2010s. Serogroup W became a significant contributor to global IMD after Hajj pilgrimage outbreaks in 2000; subsequent increases of endemic disease and outbreaks were reported pre-pandemic in many regions. Serogroup Y emerged in the 1990s as a significant cause of IMD throughout various regions and prevalence had increased or stabilized from 2010 to 2018. Serogroup X is uncommon outside the African meningitis belt, and its prevalence has declined since before the COVID-19 pandemic. Global IMD declines during the pandemic were followed by resurgences generally caused by serogroups that were prevalent pre-pandemic and affecting mainly unvaccinated age groups (particularly adolescents/young adults). Recent IMD epidemiology underscores the importance of vaccinating at-risk age groups against regionally prevalent serogroups; for example, the anti-serogroup X component of the recently prequalified MenACWXY vaccine is likely to provide limited protection outside the African meningitis belt. In other regions, comprehensive vaccination against MenB and MenACWY, which could be streamlined by the recently approved MenABCWY vaccine, seems more appropriate.